Stochastic Optimal Control, International Finance and Debt - Wendell Fleming; Jerome L. Stein (Center for Economic Studies and ifo Institute (CESifo), 2002)
We use stochastic optimal control-dynamic programming (DP) to derive the optimal foreign debt/net worth, consumption/net worth, current account/net worth, and endogenous growth rate in an open economy. Unlike the literature that uses an Intertemporal Budget Constraint (IBC) or the Maximum Principle, the DP approach does not require perfect foresight or certainty equivalence. Errors of measurement and the effects of unanticipated shocks are corrected in an optimal manner. We contrast the DP and IBC approaches, show how the results of the dynamic programming approach can be interpreted in a traditional simple mean-variance/Tobin-Markowitz context, and explain why our results are generalizations of the Merton model.
Keywords: 330; stochastic optimal control; foreign debt; international finance; vulnerability to external shocks; sustainable current account deficits